Pengaruh Institusi Regional Terhadap Konvergensi Kebijakan Antarnegara: Studi Kasus ASEAN Open Skies - Azalia, Dea Malinda (Jurnal Politik, 2017)
This article analyzes the effect of regional economic integration on cross-national policy through the ASEAN Open Skies treaty, particularly in Indonesia, Philippines, and Singapore. This qualitative research applies the concepts of intergovernmentalist-supranationalist regional institution and causal-mechanism that lead to cross-national policy convergence. I argue that ASEAN regionalism as an intergovernmentalist institution affects the process of policymaking, the implementation of ASEAN Open Skies in the regional level, and the adoption of it in the domestic level. The process of international harmonization and transnational communication (transnational problem solving) during the arrangement of the air transport cooperation frameworks in ASEAN has made the domestic policy in Indonesia, Philippines, and Singapore more similar (convergence).